Association between resting blood pressure and maximal blood pressure response to exercise and arterial health - Joensuu, Henri (2022)
We investigated the longitudinal associations of blood pressure, cardiorespiratory fitness, and arterial stiffness among children. Arterial stiffening has been repeatedly shown to be a cardiovascular mortality predictor and can be observed early in childhood. As such, it is crucial to understand whether a child’s blood pressure, fitness level, and body composition can predict early signs of atherosclerosis and arterial stiffening. The current study examined the relationship between blood pressure, cardiorespiratory fitness, and arterial stiffness over time in children, using data from the Physical and Nutrition in Children (PANIC) Study. It is a physical and dietary intervention study conducted in Kuopio, Finland. A total of 504 children participated at baseline, 277 adolescents participated at 8-year follow-up, and 201 adolescents were available for data analysis. The study measured blood pressure before and after a maximal exercise test on an ergometer. The exercise test increased in intensity until the participant reached exhaustion, and blood pressure was measured again after the test. Wave Velocity (PWV) was only measured at 8-years follow up. The main findings were that male adolescent (n=103) systolic blood pressure at rest in the supine position before to exercise, maximal workload during an exercise test, and systolic blood pressure immediately following exercise at baseline were significant predictors of pulse wave velocity in an 8-year follow-up (p<.001b ). Systolic blood pressure immediately after exercise (p=.010) and maximal workload during exercise (p=.013) were shown to be significant predictors of PWV in male adolescents only. Only females' fat mass (p=.015) and percentage of body fat (p=.016) was found to increase PWV, whereas males' lean soft tissue mass increased PWV (p=.001). The findings support the notion that blood pressure regulation and weight management should be promoted from an early age, as prevention for early signs of atherosclerosis.